Chemical Processes Involving 18‐Crown‐6‐Ether in Activated Noncovalent Complexes with Protonated Peptides. Issue 12 (18th May 2021) - Abdelmouleh, Marwa; Lalande, Mathieu; Nicol, Edith; Frison, Gilles; van der Rest, Guillaume; Poully, Jean‐Christophe
Abstract: These last decades, it has been widely assumed that 18‐crown‐6‐ether (CE) plays a spectator role during the chemical processes occurring in isolated host‐guest complexes between peptides or proteins and CE after activation in mass spectrometers. Our present experimental and theoretical results challenge this hypothesis by showing that CE can abstract a proton or a protonated molecule from protonated peptides after activation by collisions in argon or electron capture/transfer. Furthermore, thanks to comparison between experimental and calculated values of collision cross‐sections, we demonstrate that CE can change binding site after electron transfer. We also propose detailed mechanisms for these processes. Abstract : More involved than thought ! In contrast to what has been widely assumed up to now, we show that 18‐crown‐6‐ether can be involved in chemical processes triggered by activation of their noncovalent complexes with protonated peptides by collisions in argon or electron capture/transfer. Furthermore, we demonstrate that CE can change binding site after electron transfer. We also propose detailed mechanisms for these processes.